Helminthic Infections Rates and Malaria in HIV-Infected Pregnant Women on Anti-Retroviral Therapy in Rwanda - Ivan, Emil; Crowther, Nigel J.; Mutimura, Eugene; Obado Osuwat, Lawrence; Janssen, Saskia; Grobusch, Martin P. (PLoS neglected tropical diseases, 2013)
Within sub-Saharan Africa, helminth and malaria infections cause considerable morbidity in HIV-positive pregnant women and their offspring. Helminth infections are also associated with a higher risk of mother-to-child HIV transmission. The aim of this study was to determine the prevalence of, and the protective and risk factors for helminth and malaria infections in pregnant HIV-positive Rwandan women receiving anti-retroviral therapy (ART). Methodology and principle findings: Pregnant females (n = 980) were recruited from health centres in rural and peri-urban locations in the central and eastern provinces of Rwanda. Helminth infection was diagnosed using the Kato Katz method whilst the presence of Plasmodium falciparum was identified from blood smears. The prevalence of helminth infections was 34.3%; of malaria 13.3%, and of co-infections 6.6%. Helminth infections were more common in rural (43.1%) than peri-urban (18.0%; p,0.0005) sites. A CD4 count #350 cells/mm3 was associated with a higher risk of helminth infections (odds ratio, 3.39; 95% CIs, 2.16–5.33; p,0.0005) and malaria (3.37 [2.11–5.38]; p,0.0005) whilst helminth infection was a risk factor for malaria infection and vice versa. Education and employment reduced the risk of all types of infection whilst hand washing protected against helminth infection (0.29 [0.19–0.46]; p,0.0005);). The TDF-3TC-NVP (3.47 [2.21–5.45]; p,0.0005), D4T-3TCNVP (2.47 [1.27–4.80]; p,0.05) and AZT-NVP (2.60 [1.33–5.08]; p,0.05) regimens each yielded higher helminth infection rates than the AZT-3TC-NVP regimen. Anti-retroviral therapy had no effect on the risk of malaria. Conclusion/significance: HIV-positive pregnant women would benefit from the scaling up of de-worming programs alongside health education and hygiene interventions. The differential effect of certain ART combinations (as observed here most strongly with AZT-3TC-NVP) possibly protecting against helminth infection warrants further investigation.
Keywords: Helminthic Infections; Malaria; HIV; Pregnant Women; Anti-Retroviral Therapy